Partial glutathione reductase deficiency as a cause of diverse clinical manifestations in a family with unstable hemoglobin (Hemoglobin Haná, β63(E7) His-Asn) - Mojzikova, Renata; Dolezel, Petr; Pavlicek, Jiri; Mlejnek, Petr; Pospisilova, Dagmar; Divoky, Vladimir (Blood cells, molecules & diseases, 2010)
Hemoglobin Haná [β63(E7) His-Asn] is an unstable hemoglobin variant that was described in a Czech proband and her sister with Heinz body hemolytic anemia. The mother bearing the same mutation was asymptomatic; nevertheless, all three carriers had the same proportion of the mutant globin chains. Assessment of several erythrocyte antioxidant parameters revealed that both symptomatic children, unlike their asymptomatic mother, had significantly decreased glutathione reductase (GR) activity. Their GR activities were restorable in vitro by flavin adenine dinucleotide. The riboflavin supplementation improved their glutathione metabolism and ameliorated their hemolysis. Pre- and post-treatment assessment of the B(2) vitamers indicated suboptimal pre-treatment vitamin B(2) status in both children. This study provides evidence that partial GR deficiency may alter the clinical manifestation of an unstable hemoglobinopathy.
Keywords: Amino Acid Substitution; Riboflavin; rodina; Flavin-Adenine Dinucleotide; Humans; Mutation, Missense; Heinz Bodies; Family; Female; dospělí; flavinadenindinukleotid; hemoglobiny abnormální; lidé; vitamin B komplex; hemoglobinopatie; Glutathione; Adult; missense mutace; ženské pohlaví; Male; substituce aminokyselin; Vitamin B Complex; Heinzova tělíska; Adolescent; hemolytické anemie; Anemia, Hemolytic; glutathion; Glutathione Reductase; glutathionreduktasa; Hemoglobinopathies; mužské pohlaví; Hemoglobins, Abnormal; riboflavin; mladiství